Noir sensibility and the Mystical East in Amir Hafizi’s “The Unbeliever” of Amir Muhammad’s KL Noir: Red - Ririn Kurnia Trisnawati (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper examines Amir Hafizi’s “The Unbeliever”, one noir story taken from Amir Muhammad’s KL Noir: Red (2013), a noir anthology published in Malaysia. Hafizi’s “The Unbeliever” is a self-claimed noir work contained by noir sensibility with portrayals of postcolonial experiences written from the perspective of contemporary-postcolonial Malaysian society. Both its noir sensibility and postcolonial experiences constitute the darkness and alienation which are commonly associated with noir fiction. Consequently, this paper looks into noir sensibility or noir parameters that construct Hafizi’s “The Unbeliever” and, simultaneously, the inclusion of subversion of the West and East as a fragment of the postcolonial experiences that can also function as noir sensibility. The finding shows that the noir sensibility is manifested, firstly, by the noir theme comprising issues of mysticism and violence and, secondly, by the noir protagonist who is doomed and alienated. Additionally, the mystical East represented by the figure of Nyai Roro Kidul, the Queen of the Sea, has drowned the characters into darkness, chaos and, most importantly, subversion of the West and the East binary. Thus, they impressively shape this story to be a noir narrative with postcolonial issue.